Nanostructured donor-acceptor self assembly with improved photoconductivity - Saibal, B.; Ashar, A. Z.; Devi, R. Nandini; Narayan, K. S.; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Nanostructured supramolecular donor-acceptor assemblies were formed when an unsymmetrical N-substituted pyridine functionalized perylenebisimide (UPBI-Py) was complexed with oligo(p-phenylenevinylene) (OPVM-OH) complementarily functionalized with hydroxyl unit and polymerizable methacrylamide unit at the two termini. The resulting supramolecular complex [UPBI-Py (OPVM-OH)](1.0) upon polymerization by irradiation in the presence of photoinitiator formed well-defined supramolecular polymeric nanostructures. Self-assembly studies using fluorescence emission from thin film samples showed that subtle structural changes occurred on the OPV donor moiety following polymerization. The 1:1 supramolecular complex showed red-shifted aggregate emission from both OPV (similar to 500 nm) and PBI (similar to 640 nm) units, whereas the OPV aggregate emission was replaced by intense monomeric emission (similar to 430 nrn) upon polymerizing the methacrylamide units on the OPVM-OH. The bulk structure was studied using wide-angle X-ray diffraction (WXRD). Complex formation resulted in distinct changes in the cell parameters of OPVM-OH. In contrast, a physical mixture of 1 mol each of OPVM-OH and UPBI-Py prepared by mixing the powdered solid samples together showed only a combination of reflections from both parent molecules. Thin film morphology of the 1:1 molecular complex as well as the supramolecular polymer complex showed uniform lamellar structures in the domain range <10 rim. The donor-acceptor supramolecular complex [UPBI-Py (OPVM-OH)](1.0) exhibited space charge limited current (SCLC) with a bulk mobility estimate of an order of magnitude higher accompanied by a higher photoconductivity yield compared to the pristine UPBI-Py. This is a very versatile method to obtain spatially defined organization of n and p-type semiconductor materials based on suitably functionalized donor and acceptor molecules resulting in improved photocurrent response using self-assembly.
Keywords: donor-acceptor; hydrogen bonding; oligo(p-phenylenevinylene); Perylenebisimide; photoconductivity; supramolecular polymeric nanostructures

P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility - Saibal, B.; Chithiravel, Sundaresan; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Random donor-acceptor (D-A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN-OH) and Perylenebisimide (named UPBI-PDP), respectively, were complexed with Poly(4-vinyl pyridine) (P4VP). A series of random D-A supramolecular comb polymers were formed by varying the ratios of UPBI-PDP and OPVCN-OH with P4VP. A 100% P4VP-donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP-acceptor polymer complex [P4VP(UPBI1.00)] were also synthesized and characterized. Complex formation was confirmed by FT-IR and H-1 NMR spectroscopy. Solid state structural studies carried out using small angle X-ray scattering and wide angle X-ray diffraction experiments revealed altered packing of the D and A molecules in the complexes. Transmission electron microscopy images showed lamellar structures in the <10 nm scale for the P4VP(OPV1.00), P4VP(UPBI1.00), and mixed P4VP (D-A) complexes. The effect of the nanoscopic D-A self-assembly on the bulk mobility of the materials was probed using SCLC measurements. The mixed D-A random complexes exhibited ambipolar charge transport characteristics with higher values for the average bulk hole mobility estimate. P4VP(OPV0.25+UPBI0.75) exhibited an average hole mobility in the order of 10(-2) cm(2) V-1 s(-1) and electron mobility 10(-5) cm(2) V-1 s(-1). (C) 2016 Wiley Periodicals, Inc.
Keywords: donor-acceptor; oligo(phenylenevinylene); P4VP; Perylenebisimide; Self-assembly; structure-property relations; supramolecular comb polymer; supramolecular structures

Liquid crystalline supramolecular crosslinked polymer complexes of ditopic rylenebisimides and P4VP - Saibal, B.; Narayan, Rekha; Chithiravel, S.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Perylenebisimide and naphthalenebisimide (PBIPDP and NBI-PDP) end functionalized with pentadecyl phenol is designed as ditopic hydrogen bonding acceptors to form supramolecular crosslinked network with poly(4-vinyl pyridine) (P4VP). The pristine PBI-PDP has been grown as single crystals from DCM-MeOH (dichloromethane-methanol) mixture at room temperature, which revealed a P21 space group. Noticeably, the pentadecyl alkyl chain shields the aromatic perylene core on both sides resulting in the absence of p-p interaction in single-crystal assembly. The naphthalenebisimide derivative exhibits thermotropic liquid crystalline behavior, while both the molecules exhibits lyotropic liquid crystalline phases in tetrahydrofuran (THF), which were characterized using a combination of differential scanning calorimeter, X-ray diffraction, and polarized light microscopy. The hydrogen-bonded complex of both the rylenebisimides with P4VP preserves the mesomorphic properties in THF. The electron transport mobility measured by space charge limited current measurements reveals a two orders of magnitude increase in the charge transport in the P4VP complex compared to that of the pristine molecule. The average electron mobility obtained is mu(e, avg): 10(-3) cm(2)/Vs for P4VP-PBI compared to mu(e, avg): 10(-5) cm(2)/Vs for pristine PBI derivative. (C) 2017 Wiley Periodicals, Inc.
Keywords: crystal structures; ditopic rylenebisimide; hydrogen bonding; lyotropic liquid crystal; P4VP; Self-assembly; supramolecular crosslink; supramolecular structures